2016
DOI: 10.1161/circulationaha.116.022684
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous Device Closure of Paravalvular Leak

Abstract: Percutaneous closure of PVL is an effective procedure that improves PVL severity and symptoms. Severity of persisting leak at follow-up is independently associated with both MACE and death. Percutaneous closure should be considered as an alternative to repeat surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 16 publications
1
42
1
2
Order By: Relevance
“…For this reason some conclude that the transapical approach could be considered as a first line therapy [ 23 , 24 ] . Other authors state that this approach allows access to defects in all anatomic locations of the mitral prosthesis [ 3 ]. Furthermore, the analysis by Jelnin et al showed that a planned transapical approach resulted in shorter fluoroscopy and procedural times compared with the converted and combined trans-septal procedures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason some conclude that the transapical approach could be considered as a first line therapy [ 23 , 24 ] . Other authors state that this approach allows access to defects in all anatomic locations of the mitral prosthesis [ 3 ]. Furthermore, the analysis by Jelnin et al showed that a planned transapical approach resulted in shorter fluoroscopy and procedural times compared with the converted and combined trans-septal procedures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of definitions to establish disease severity and endpoints for the safety and efficacy of PVL treatment there is currently an absence of outcomes for PVL treatment modalities in the literature [ 2 ]. Available data are very heterogeneous, with different devices being used, various access sites being employed for different valve prostheses, and mostly short-term outcomes are presented [ 3 5 ]. The specifically designed and manufactured Occlutech PLD Occluder for PVL closure has been introduced into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Various percutaneous and hybrid techniques have been developed over the last years to address paravalvular regurgitation avoiding redo sternotomy, CPB, and aortic cross-clamp ( 14 , 17 ). Randomized controlled trials comparing surgical and catheter closure of PVL are not currently available; however, early mortality in elective cases was reported to be 2.9% in a recent large series from UK and Irish centers ( 18 ). To our knowledge, there are no published series reporting results of transcatheter PVL closure in adults with previous diagnosis of atrioventricular septal defect.…”
Section: Discussionmentioning
confidence: 99%
“…While PVL can affect any valve, it is more common with mitral mechanical prostheses . Recent reports suggest that successful percutaneous repair of mitral PVL is associated with long term survival benefit and with less major adverse cardiovascular events . The 2014 American College of Cardiology/American Heart Association guidelines for the management of valvular heart disease recommended percutaneous repair of PVL (Class IIa) for high‐risk surgical patients with either intractable hemolysis or New York Heart Association (NYHA) class III or IV heart failure .…”
Section: Introductionmentioning
confidence: 99%